A comparative analysis of sequence composition in different lots of a phage display peptide library during amplification - Anders Wilgaard Sinkjaer; Ane Beth Sloth; Amanda Oester Andersen; Malte Jensen; Babak Bakhshinejad; Andreas Kjaer (Virology Journal)
Abstract Background To develop efficient selection strategies and improve the discovery of promising ligands, it is highly desirable to analyze the sequence composition of naïve phage display libraries and monitor the evolution of their peptide content during successive rounds of amplification. In the current study, we performed a comparative analysis of the compositional features in different lots of the same naïve phage display library and monitored alterations in their peptide compositions during three rounds of amplification. Methods We conducted three rounds of duplicate serial amplification of two different lots of the Ph.D.™-12 phage display library. DNA from the samples was subjected to Next-Generation Sequencing (NGS) using an Illumina platform. The NGS datasets underwent a variety of bioinformatic analyses using Python and MATLAB scripts. Results We observed substantial heterogeneity in the sequence composition of the two lots indicated by differences in the enhanced percentage of wildtype clones, reduced diversity (number of unique sequences), and increased enrichment factors (EFs) during amplification as well as by observing no common sequence between lots and decreased number of common sequences between the naïve library and the consecutive rounds of amplification for each lot. We also found potential propagation-related target-unrelated peptides (TUPs) with the highest EFs in the two lots, which were displayed by the fastest-propagating phage clones. Furthermore, motif analysis of the most enriched subpopulation of amplified libraries led to the identification of some motifs hypothesized to contribute to the increased amplification rates of the respective phage clones. Conclusion Our results highlight tremendous heterogeneity in the peptide composition of different lots of the same type of naïve phage display library, and the divergent evolution of their compositional features during amplification rounds at the amino acid, peptide, and motif levels. Our findings can be instrumental for phage display researchers by bringing fundamental insights into the vast extent of non-uniformity between phage display libraries and by providing a clear picture of how these discrepancies can lead to different evolutionary fates for the peptide composition of phage pools, which can have profound impacts on the outcome of phage display selections through biopanning.